Analysis of Factors for the Use of University e-Learning Through the E-learning Readiness Model Approach - Cesario Auditya Pratama Putra; Sfenrianto (Postgraduate, University of Mataram, 2025)
This study aims to analyze the factors influencing the use of e-learning as a learning medium at University X in Jakarta. With the increasing demand for distance education programs, the readiness of the institution to implement e-learning is crucial. This research is a research with a quantitative approach. Data collection techniques using questionnaire instruments in data and information collection. The model determination stage is an important step in the research process where the authors select and develop a suitable model to evaluate the use of e-learning in the readiness to open a distance learning program at university. This research employs the E-learning Readiness Model, encompassing technical, pedagogical, and social aspects. A survey method was utilized, distributing questionnaires to students and faculty members. The findings indicate that factors such as technological infrastructure, academic support, and user attitudes significantly impact e-learning usage. These results are expected to serve as a foundation for University X in designing and implementing effective distance education programs.